1990
DOI: 10.1071/ch9901587
|View full text |Cite
|
Sign up to set email alerts
|

6-O-Methylarthothelin and 1,3,6-Tri-O-Methylarthothelin, Two New Xanthones From a Dimelaena Lichen

Abstract: 6-O-Methylarthothelin (5) (2,4,5-trichloro-1,3-dihydroxy-6-methoxy-8- methyl-9H-xanthen-9-one) and 1,3,6-tri-O-methylarthothelin (7) (2,4,5- trichloro-1,3,6-trimethoxy-8-methyl-9H-xanthen-9-one) have been synthesized and shown to cooccur with norstictic acid, connorstictic acid, atranorin and 2,4,5-trichlorolichexanthone (4) in a Dimelaena lichen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…The structure of the latter was confirmed by the treatment of 19 with excess dimethyl sulfate, giving a trimethylated product, identical with 23 . The authors further isolated two minor xanthones from the same species but were unable to attribute structures . In the same year, Elix and co-workers reported the synthesis and therefore structural confirmation of isoarthothelin utilizing a Friedel–Crafts pathway, which which allowed them to correct previous reports of the occurrence of this compound in Lecanora sulphurata and L. flavo-pallescens . ,, …”
Section: Monomersmentioning
confidence: 96%
See 2 more Smart Citations
“…The structure of the latter was confirmed by the treatment of 19 with excess dimethyl sulfate, giving a trimethylated product, identical with 23 . The authors further isolated two minor xanthones from the same species but were unable to attribute structures . In the same year, Elix and co-workers reported the synthesis and therefore structural confirmation of isoarthothelin utilizing a Friedel–Crafts pathway, which which allowed them to correct previous reports of the occurrence of this compound in Lecanora sulphurata and L. flavo-pallescens . ,, …”
Section: Monomersmentioning
confidence: 96%
“…In 1990 Elix and Bennett reported the isolation of two new arthothelin derivatives from the lichen Dimelaena cf. australiensis sp., alongside several other compounds and the known xanthone, 2,4,5-trichlorolichexanthone ( 74 , Figure ) . They were 6- O -methylarthothelin ( 22 , also isolated from Micarea isabellina ) and 1,3,6-tri- O -methylarthothelin ( 23 , from Dimelaena sp .…”
Section: Monomersmentioning
confidence: 98%
See 1 more Smart Citation
“…Xanthones are synthesized by plants, bacteria, and fungi (10,13) and can contain a range of substitutions, including hydroxyl, methyl, and chloro groups (10,11,12). A total of 38 xanthones have been identified that contain between 1 and 4 chlorines (11,12). Interestingly, the basic chemical structure of chlorinated xanthones resembles that of the anthropogenic chlorinated pollutants polychlorinated biphenyls (PCBs) and dibenzo-p-dioxins (dioxins) (Fig.…”
mentioning
confidence: 99%
“…Studies on the degradation of naturally occurring organochlorines, however, are generally lacking. Xanthones are a group of naturally occurring compounds that may be particularly abundant in some environments (10,11,12,13). Xanthones are synthesized by plants, bacteria, and fungi (10,13) and can contain a range of substitutions, including hydroxyl, methyl, and chloro groups (10,11,12).…”
mentioning
confidence: 99%